EXPOSITORY METHOD AIDED APPLICATION POWER POINT TO INCREASE OF LEARNING MATH CLASS VII SMPN 3 MANDE LINEAR EQUATION IN ONE VARIABLE MATERIAL - Fratama, Eva Julia; Zain, Ella Nurlatifah Rusyani; Maulani, Rizky Laili (IAPM UNSUR (Ikatan Alumni Pendidikan Matematika Universitas Suryakancana))
This research is the Classroom Action Research (CAR). This study aims to improve student learning outcomes using the expository method assisted powerpoint.This method is a method of learning that is used to provide information beforehand definitions, principles and concepts of the subject matter as well as provide examples of problem-solving exercises in the form of lectures, demonstrations, discussion and assignments were aided by using media powerpoint. This research was conducted at SMPN 3 Mande Cianjur academic year 2017/2018 with the subject of class VII-B, amounting to 32 students. This study was done three cycles. Each cycle held three meetings of three times and three times in the test learning. The instruments used in data collection is a task (task group and individual assignments in class), tests and observation. Data were analyzed using descriptive statistics such as average and percentage. The results showed the average value of student learning outcomes in the first cycle to the second cycle increased by 2.81% from the value of the first cycle is 70,63. In the third cycle, the average value of student learning outcomes decreased by 2.19% from the average value of the second cycle of student learning outcomes, namely 73.44 into 71.25. In addition, the third cycle, the average value of student learning outcomes increased by 0.63% from the average value of student learning outcomes become the first cycle is 70,63 71.25. Activities of students in the first cycle is quite active, relatively inactive in the second cycle and the third cycle classified as active. Based on these results, we can conclude that the increase in students' mathematics learning outcomes through expository method aided by a power point with material linear equations in one variable of class VII SMPN 3 Mande increased.